1996
DOI: 10.1136/fn.75.3.f174
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral palsy and multiple births.

Abstract: Aim-To compare the birthweight specific prevalence of cerebral palsy in singleton and multiple births.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
81
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(87 citation statements)
references
References 8 publications
4
81
1
1
Order By: Relevance
“…Twinning has been recognized as a risk factor for CP for at least a century [15]. The CP rate per 1000 is 2.3 in singleton survivors, 12.6 in twins and 44.8 in triplets, demonstrating an increased risk in higher order multiple pregnancies [16]. Thus CP is at least five times more frequent among twins than singleton.…”
Section: Neurodevelopmental Outcomesmentioning
confidence: 99%
“…Twinning has been recognized as a risk factor for CP for at least a century [15]. The CP rate per 1000 is 2.3 in singleton survivors, 12.6 in twins and 44.8 in triplets, demonstrating an increased risk in higher order multiple pregnancies [16]. Thus CP is at least five times more frequent among twins than singleton.…”
Section: Neurodevelopmental Outcomesmentioning
confidence: 99%
“…These abnormalities in the surviving fetus, almost invariably, have been reported in monochorionic twin pregnancies (Anderson et al, 1990;Baker & Doering, 1982;Grafe, 1993;Hoyme et al, 1981;Scheller & Nelson, 1992;Schinzel et al, 1979). The risk of cerebral palsy in the surviving twin of a co-twin that died in utero is about 1 in 10 (Grether et al, 1993;Pharoah & Cooke, 1996;Pharoah & Adi, 2000). It has been hypothesized that the early demise of an embryo or fetus that is unrecognized or unregistered is the cause of many congenital anomalies, including cerebral palsy, in singleton births (Pharoah, 2005).…”
Section: Twin Research and Human Genetics August 2006mentioning
confidence: 97%
“…Intrauterine Growth and Cerebral Palsy in Twins births (Grether et al, 1993;King & Johnson, 1995;Liu et al, 2000;Nelson & Ellenberg, 1995;Petterson et al, 1993;Pharoah & Cooke, 1996;Stanley et al, 2000b;Williams et al, 1996;Yokoyama et al, 1995). However, only some of these studies reported CP rates by gestational age (Liu et al, 2000;Pharoah & Adi, 2000;Scher et al, 2002;Williams et al, 1996;Yokoyama et al, 1995).…”
Section: Twin Research and Human Genetics June 2006mentioning
confidence: 99%
“…Twins and higher order multiples are at greater risk of neurological morbidity than singletons. Thus, the prevalence of CP ranges from 7 to 12 per 1000 survivors in twins, compared with one to two in singletons (Grether et al, 1993;Petterson et al, 1993;Pharoah & Cooke, 1996;Williams et al, 1996;Yokoyama et al, 1995). The higher rate of CP in twins can not be entirely attributable to the higher proportion of low birthweight and preterm infants among twins, because the risk of CP in twins is also higher in normal birthweight twins compared to singletons of similar birthweight (Grether et al, 1993;Pharoah & Cooke, 1996;Williams et al, 1996).…”
mentioning
confidence: 99%
See 1 more Smart Citation